A hundred-year journey and a return to our roots: occupation, adaptation through occupation, and client-centeredness - Grajo, Lenin C.; Cruz, Daniel Marinho Cezar da (Cadernos Brasileiros de Terapia Ocupacional, 2017)
The year 2017 marks a very special milestone for the whole international community of occupational therapy. The American Occupational Therapy Association (AOTA) celebrated the centennial of occupational therapy in the United States with its annual conference held last March 30 – April 2, 2017 at the Pennsylvania Convention Center in Philadelphia. The conference had a record number of 13,000 attendees, with representation from approximately 20 different nations. Brazil had one paper presented in the category research panel (CRUZ; CARO, 2017). As we continue celebrating the centennial anniversary of the founding of occupational therapy, it is also a critical time to reflect on what we want for the profession in the future and the challenges we will need to accept. The AOTA in 2016 has adopted Vision 2025, which builds on the work of the Centennial Vision to guide the profession beyond 2017: “Occupational therapy maximizes health, well-being, and quality of life for all people, populations, and communities through effective solutions that facilitate participation in everyday living” (AMERICAN..., 2017, p. 1). In promoting what we do as occupational therapists in daily practice, are we articulating some important constructs that have been part of our profession since its founding? Here, we focus on three constructs as a start: occupation, occupational adaptation, and client-centeredness. Occupation. This is the fundamental construct of our profession, as emphasized by Reilly’s famous quote “Man through the use of his hands as they are energized by mind and will, can influence the state of his own health” (REILLY, 1961, p. 2). Pizzi and Richards (2017) further noted that since the inception of occupational therapy, there has always been a link between occupation and health, well-being, and quality of life. They further challenged us that “[...] if occupational therapy does not focus on these concepts, other professions will happily do so” (PIZZI; RICHARDS, 2017, p. 4). How do we use and articulate occupation as a fundamental construct in our profession? Are we comfortable using the language of occupation when promoting our distinct value to our stakeholders? Occupational participation not only has an impact on health and well-being but on another important construct in our profession: adaptation through occupation. Occupational Adaptation. A commonly under-articulated construct in practice is occupational adaptation. Occupational adaptation is an internal human process that occurs as we participate in occupation and transact with our environment; it is a process of responding to change and life transitions that influences the formation of a desired sense of self (GRAJO; BOISSELLE; DALOMBA, in press). The therapeutic process, a powerful event, may facilitate or hinder the adaptiveness of our clients. When we treat our clients, are we promoting ‘doing by’ or ‘doing to’ the client? Do we allow our clients to be their own agents of change during therapy? Are we enabling them to make critical decisions about the goals they set, the roles to prioritize, and the outcomes they want to achieve, thereby facilitating their occupational adaptation? Client-centeredness, our next construct, is critical in facilitating occupational adaptation. Client-centeredness. Elizabeth Yerxa, in her 1966 Slagle Lecture, described that “[...] authentic occupational therapy is based upon a commitment to the client’s realization of his own particular meaning” (YERXA, 1967, p. 8). She added that “choice” and “self-initiated purposeful activity” are what makes our profession unique. Often times, with the pressure of increased productivity and decreased therapy times devoted for our clients, we often neglect the value of choice and self-initiated goals and occupations. Are we promoters of protocols or an individualized approach to therapy? How often have we forgotten to provide our clients choice in their care and priorities in life? Are we being authentic to the philosophies of our profession by being client-centered all the time? Conclusion We are living at present in a politically complex, global world faced daily with inequalities, social and occupational injustices, corruption, espionage, terrorism and violence. The new era of technology addiction and access to social media puts us all together in real time with ready access to information almost as if we are living side by side with our neighbours. How does this affect our relationship with our clients and our practice? How can we remain faithful to the historical roots and values of occupational therapy amidst globalization, internationalization, modernization, and ever-changing socio-political factors? Finally, in Brazil, occupational therapy celebrates half a century of its founding, yet there is a long way to go in building occupational therapy in areas such as: more researchers working in public universities, international cooperation for projects in communities, developing new and emerging fields of practice, and many other things to try to create a distinctive Brazilian field of occupational therapy in both theory and practice. We all need to be globally connected and work together to share our concerns, solutions, ideas, hopes and wishes as this will have an impact on occupational therapy education, clinical practice and research. Shall we start now? We (Lenin and Daniel) have started already! Lenin C. Grajo, PhD, EdM, OTR/L Columbia University Medical Center, New York, NY, USA. Assistant Professor of Rehabilitation and Regenerative Medicine Daniel Marinho Cezar da Cruz, PhD, OTR Universidade Federal de São Carlos – UFSCar, São Carlos, SP, Brazil. Editor in Chief/ Brazilian Journal of Occupational Therapy